Diseminasi Moderasi Beragama Melalui Pendidikan Agama Islam pada Ekstrakurikuler Sie Kerohanian Islam (ROHIS) di SMAN 1 Kertosono Kabupaten Nganjuk - Saini, Mukhamat (TABYIN: JURNAL PENDIDIKAN ISLAM, 2021)
In some areas it has been found that Islamic spiritual organizations have been contaminated by radical ideas that oppose state ideology. Not infrequently some of the material delivered through political orientation to attitudes towards religious organizations or other religions. Islamic Spirituality (ROHIS) is a strategic organization to instill and foster the values ​​of moderation. The Islamic spirituality (ROHIS) activity at SMAN 1 Kertosono has contents that become certain characteristics of religious character. ROHIS activities at SMAN 1 Kertosono are related to the content of studying religion, namely developing noble character, and also developing students' religious knowledge more deeply. Dissemination of religious moderation can be viewed in terms of the material presented, several things can shape students' religious moderation attitudes, including; manners, morals and mutual respect for each other. The objectives of this study are, first, to describe the role of extracurricular Islamic spirituality (ROHIS) at SMAN 1 Kertosono. Second, describe the formation of religious character through ROHIS at SMAN 1 Kertosono. Third, actualizing religious moderation through Islamic Religious Education (PAI) in Islamic spirituality extracurricular (ROHIS) at SMAN 1 Kertosono. This research uses qualitative research with case study type, data collection methods used are observation, interviews and documentation. Data analysis techniques in this study are data collection, data reduction, data presentation, conclusion and verification. Checking the validity of the data using credibility, transferability, dependability and confirmability. The conclusion from the results of this study is that first, the role of ROHIS extracurricular activities at SMAN 1 Kertosono can shape the religious character of students through several activities. Namely, ramadhon cottage activities, tahfidz activities, routine studies and congregational prayer activities. Second, the character building of ROHIS extracurricular activities at SMAN 1 Kertosono also emphasizes tolerant and moderate Islam. Where students when they have received lessons from ROHIS extracurriculars through Islamic religious education teachers (PAI), then students are more confident and able to practice the teachings of Islam. Third, the actualization of religious moderation shows that the management of ROHIS SMAN 1 Kertosono has a passive tolerance category. The indicator that is fulfilled is that the ROHIS SMAN 1 Kertosono management accepts and respects the differences shown by various moderate attitudes towards followers of other religions.